Effect of Sowing Date and Seedling Thickness on Main Stem Height, Total Leaf Area, Formation of Side Branches, Green Leaf Yield of Stevia (Texas Journal of Agriculture and Biological Sciences, 2023)
this article provides information on the dead of sowing a stevia plant in conditions of light gray soils and the influence of seedling thickness on the height of the main stem, the surface of the total leaf level, the formation of side branches, the effect on the green leaf yield.